Family-based intervention to prevent childhood obesity among school-age children of low socioeconomic status: study protocol of the FIVALIN project - C. Homs; P. Berruezo; G. Según; L. Estrada; J. de Bont; J. Riera-Romaní; E. Carrillo-Álvarez; H. Schröder; R. Milà; S. F. Gómez (BMC, 2021)
Abstract Background Childhood obesity represents a global public health crisis: the number of obese children and adolescents (aged 5-19 years) worldwide has risen tenfold in the past four decades. The vast majority of overweight and obese children live in high-income countries, and low socio-economic status (SES) is a significant risk factor. Family Based Interventions (FBI) have demonstrated positive results in preventing obesity, although these results are strongly influenced by SES. Moreover, we still poorly understand how FBI can determine a positive trend in weight status in low-income communities. Therefore, there is an urgent need to define and evaluate innovative and multi-target projects to reduce obesity risk behaviors and health inequalities and the present study aims to present the study protocol of FIVALIN a FBI that pretends to achieve this goal. Methods We will conduct a quasi-experimental design within 60 Community Child Centers (CCC) in Barcelona metropolitan area. Each cluster (CCC) will be assigned by convenience to the intervention and control groups. For the whole study, a total of 810 children aged 8-12 years and 600 parents will be recruited during 3 consecutive editions (1st - 2019/2020; 2nd - 2020/2021; 3rd - 2021/2022) of 10 months each. The action is a regular multicomponent health-promotion intervention targeting children, families, and CCC. All activities are based on the Motivational Interviewing (MI) approach and will focus on promoting good dietary habits, physical activity, appropriate screen time and sleep duration, and psychological well-being. The control group participate in a unique workshop on general awareness of healthy lifestyles for families. We will perform a comparative analysis of the evolution of weight status, healthy lifestyles, and socioeconomic variables, between the intervention and control groups. Discussion There is a need for more evidence on how to target and evaluate holistic interventions in low SES families. Our multi-targeting intervention for obesity prevention tackles risky behaviors that go beyond diet and physical activity (PA). Therefore, future interventions can effectively promote all the behavioral domains that determine trends in the weight status. Trial registration ISRCTN Registry: ISRCRN12682870 . Registered 9 July 2020. Retrospectively registered. Protocol version: 30 April 2021, version 5.